Concentrating all helper protein functions on a single entity allows rescue of recombinant measles virus by transfection of just two plasmids. (28th November 2022) - Auste, Arne; Mühlebach, Michael D.
Abstract : The generation of recombinant measles virus (MeV) from manipulated genomes on plasmid DNA is quite a complex and inefficient process. As a member of the order Mononegavirales its single-stranded ssRNA genome in negative sense orientation is not infectious, but requires co-availability of the viral RNA-dependent RNA polymerase L, the polymerase co-factor phosphoprotein P, and the nucleocapsid protein N in defined relative amounts to establish infectious centres in transfected cell cultures that release replication-competent recombinant MeV particles. For this so-called rescue, different rescue systems were developed that rely on at least four different components. In this work, we establish a functional MeV rescue system just being composed of two components: the plasmid encoding the (modified) viral genome, and a one-helper-plasmid bundling all helper functions. In contrast to a rescue-system for Newcastle Disease Virus, another paramyxovirus, co-expression of all helper proteins by the same promoter failed. Instead, adaptation of the strength of the respective promoters to drive each helper gene´s expression to the relative expression found in MeV-infected cells or other rescue systems, which indeed adjusted respective mRNA and protein expression, yielded success, albeit not yet to the same efficacy as the four-component system. Thereby, our study paves the way for the development of easier and, after further optimization, more efficient rescue systems to generate recombinant MeV for e.g. the application as a vaccine platform or oncolytic virus, for example.